Aprendizaje proactivo intraclase en estudiantes de décimo año de educación General básica de la unidad educativa Zoila Ugarte de Landívar, de Santa Rosa, 2013-2014. - Canga León, Maira Moraima (2014)
The research development allowed to conclude that students' learning is affected as they are not complemented by cognitive activities or those are inadequate, adding to the little influence of the family who remains isolated from the student's school and social environment.